La semiotica della casuistica / The Semiotics of Casuistry - Maani, Sitti (Rivista Italiana di Filosofia del Linguaggio, 1970)
From the second half of the sixteenth century until the second half of the seventeenth, a new way of interpreting the religious tradition and constructing the moral discourse developed in the Catholic culture and, to a lesser extent, also in the Protestant one. This new way, predominantly but not exclusively practiced by the Jesuits, coincided with the discursive genre of casuistry. Casuistry consisted in the attempt at reconciling the interpretation of tradition with the advent of modernity, that is, in the attempt at altering the shape of religious culture so that it might adapt to the new sociocultural tendencies of modern Europe. In the frame of this re-articulation of religious culture, casuistry also proposed a new conception of signs and, in particular, of the relation between society, religion, and language. The article focuses on a passage (tome I, lesson XLIV) from the Lezioni sacre of the Jesuit Carlo Ambrogio Cattaneo (1645-1705), in which he proposed considerations on the arbitrary character of languages that, from a certain point of view, anticipate some reflections of Ferdinand de Saussure. These considerations ignited a polemic that produced about twenty works on such theme. Thus far, this important page in the history of the philosophy of language has been almost completely ignored.